2013
DOI: 10.5296/ijafr.v3i1.2994
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Various Earnings and Cash Flow Measures of Firm Performance and Stock Returns: some Iranian evidence

Abstract: The main purpose of this research is the study of association between various measures of firm performance based on earnings and cash flows and stock returns. This research is an applied research, and its design is semi-empirical, which is done by the method of post-event (past information). The statistical population of the research includes all companies listed in Tehran Stock Exchange (TSE), and its period is nine consecutive years, from 2003 to 2011. Simple and multiple regressions are applied in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These results were consistent with the findings of Oshodin and Chijoke (2014). Also, earnings-based measures were reported to be relevant than cash flow measures by Mazloom (2013) in Iran. In East Africa, particularly in Kenya, Kairuki and Oyugi (2013) found that return on equity and book value per share were relevant in explaining variation in stock prices, while Nyabundi (2013) found that dividend per share was relevant, consistent with the findings of Oyerinde (2009) in Nigeria.…”
Section: Review Of Literaturementioning
confidence: 95%
“…These results were consistent with the findings of Oshodin and Chijoke (2014). Also, earnings-based measures were reported to be relevant than cash flow measures by Mazloom (2013) in Iran. In East Africa, particularly in Kenya, Kairuki and Oyugi (2013) found that return on equity and book value per share were relevant in explaining variation in stock prices, while Nyabundi (2013) found that dividend per share was relevant, consistent with the findings of Oyerinde (2009) in Nigeria.…”
Section: Review Of Literaturementioning
confidence: 95%
“…• The cash flow ratios chosen in the analysis are simple ratios that were used for comparison purposes. Mazloom et al (2013) pointed to the relationship between the different measures used to evaluate the company's performance, and therefore performance measures can be divided into two groups-financial and nonfinancial measures-which can be used together and, accordingly, the research variables are represented in (operating profit -net operating profit plus depreciations -net profit after tax ratio -net cash flow from operating, investing, and financingstock returns -accruals). The study period is 9 years from 2003-2011, and the study community is all companies included in the Tehran Stock Exchange for the exchange of shares.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Whereas, Watson and Wells (2005) find the relationship between the cash flow and operating performance was negative and statistically significant. The relationships between profit and cash flow variables in the Iran stock market have been analyzed by Mazloom et al (2013). Multi-variable method for analyzing regression using data from 2003 to 2011.…”
Section: Impact Of Cash Flow On Operational Efficiencymentioning
confidence: 99%